2016
DOI: 10.3233/jbr-160118
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacterial endophytes from Actinidia chinensis and preliminary studies on their possible use as antagonists against Pseudomonas syringae pv. actinidiae

Abstract: Abstract:BACKGROUND:The bacterial canker, caused by Pseudomonas syringae pv. actinidiae, is the most severe disease of cultivated Actinidia spp. The pathogen is systemic and not easily controlled by agrochemical means. OBJECTIVE:Our aim was to search, select and identify, among kiwifruit bacterial endophytes, possible antagonists able to control Pseudomonas syringae pv. actinidiae. METHODS:Several kiwifruit production areas were inspected, in order to find host plants without any disease symptom inside severel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A possible and safe alternative to manage Monilinia fruit decays is biological control using antagonistic microorganisms often isolated from food sources and from natural environment in which they compete with pathogenic epiphytic microorganisms (Grzegorczyk et al, 2017;Tontou et al, 2016a). Also bacterial endophytes, which provide important benefits to plants, might be deserved for developing innovative and sustainable biocontrol strategies (Compant et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible and safe alternative to manage Monilinia fruit decays is biological control using antagonistic microorganisms often isolated from food sources and from natural environment in which they compete with pathogenic epiphytic microorganisms (Grzegorczyk et al, 2017;Tontou et al, 2016a). Also bacterial endophytes, which provide important benefits to plants, might be deserved for developing innovative and sustainable biocontrol strategies (Compant et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…P. synxantha DLS65, isolated from kiwi tissues in the region of Emilia Romagna, Italy (Tontou et al, 2016a), and genotipically characterized (Tontou et al, 2016b), was maintained in 15% glycerol at -80°C and subcultured on Nutrient Agar medium (NA, Oxoid, Basingstoke, UK) at 25 ± 1°C.…”
Section: Pseudomonasstrainmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocontrol strategies, such as the use of antagonistic bacteria, like Bacillus subtilis, Pantoea agglomerans , and Lactobacillus plantarum , have shown promising results against Psa in in vitro conditions [ 14 , 15 , 16 ]; however, the efficacy of this approach to control Psa infection in commercial field conditions was less consistent [ 15 , 17 , 18 , 19 ]. Bacteriophages have also been assayed as controlling agents against phytopathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Present studies of Psa are mainly focused on species classification [ 7 , 44 ], molecular biology [ 45 47 ], analysis of biological characteristics [ 48 , 49 ], pathogenicity differentiation[ 50 – 52 ], rapid detection methods [ 48 , 53 , 54 ], and disease control [ 55 , 56 ]; however, systemic research about the influence of climate change on the niches specific to Psa is lacking. In an effort to analyze the effects of climate change on the potential distribution of Psa, MaxEnt was utilized to model the current niches of Psa in China, as well as the future Psa niches under climate change scenarios; additionally, this study identified climatic variables important for the potential establishment of Psa.…”
Section: Introductionmentioning
confidence: 99%